10-Month characterization of the aerosol number size distribution and related air quality and meteorology at the Bondville, IL Midwestern background site. (April 2017) - Bullard, Robert L.; Singh, Ashish; Anderson, Sybil M.; Lehmann, Christopher M.B.; Stanier, Charles O.
Abstract: The aerosol size distribution was measured at a rural continental U.S. location (Bondville, Illinois 40.05 ∘ N and 88.37 ∘ W) for the period July 2013–June 2014. The dehumidified size distribution in the range 3 nm to 2.5 μm was continuously recorded by two scanning mobility particle sizers and an aerodynamic particle sizer. The Illinois measurement site is significant because it is home to one of the longest records (20+ years) in North America of atmospheric aerosol, meteorology, and gas phase variables. It is a common site for model-measurement comparison of both chemical and aerosol microphysical variables. However, while the measurement record has aerosol number concentration and optical properties, the number size distribution has not been well-constrained. Measurement highlights include means in number concentration (3–2500 nm), aerosol optical depth, S O 2, N H 3, and PM 2.5 of 6500 cm −3, 0.18, 0.87 ppb, 1.6 ppb, and 8.8 μg m −3, respectively. The mode in the mean size distribution was 31 nm (number) and 287 nm (volume). The mean size distribution was heavily influenced by nuclei mode particles, with 46% of particles smaller than 20 nm. New particle formation and growth events increase midday concentrations of 3–50 nm particles substantially, with the highest activity in spring months and lower activity in summer and winter. Short term elevations in particle number and mass associated with local agricultural burning in April are reported as well. Graphical abstract: Highlights: Size distribution for 10 months collocated with long-term monitoring networks. Peak hourly mass concentrations due to agricultural burning in spring. Peak number concentrations are due to new particle formation events in spring. Hourly dataset, ranging from monthly means of 2, 990–9, 760 cm −3, is online.